KEMAMPUAN PENGUASAAN MAJAS PERTENTANGAN SISWA KELAS XII SMK KESEHATAN SAHATA KOTA PEMATANGSIANTAR - Dedi Zulkarnain Pulungan (Universitas Negeri Medan, 2014)
Figure of speech CONFLICT CONTROL CAPABILITIES HEALTH CLASS XII SMK SAHATA CITY PEMATANGSIANTAR LESSONS YEAR 2014-2015 DEDI ZULKARNAIN Pulungan NIM : 8136192007 FIELD STATE UNIVERSITY GRADUATE INDONESIAN ABSTRACT The research was conducted in SMK SAHATA Health Academic Year 2014-2015 100 City Road Melanthon siregar Pematangsiatar.dengan penelitain Methods Descriptive . This study aimed to describe the ability of opposition figure of speech in a sentence mastery class XII student of SMK HEALTH SAHATA Pematangsiantar 2014-2015 academic year of calculation of the percentage figure of speech known mastery ability opposition in class XII student sentence quite able to value - average ( mean ) 70.33 . Students were categorized memproleh value (A) there is as much as 33.33 % gain value (B) there is as much as 26.67 % , gain value (C) there is as much as 20 % , memproleh value (D) there are as many as 20 % and category value (E) there as much as 0 % .From the results of the analysis of data and the number of students who meet the criteria of completeness of the results of the ability to master figure of speech in a sentence contradictions exist in both categories with the amount of 80 %. Keywords : Mastery opposition figure of speech